Chapter Авантуре и авантуристи у Зелићевом Житију - Grdinić, Nikola (Biblioteca di Studi Slavistici, 2019)
Between the 18th and 19th centuries adventurism became a staple part of the bourgeois ideology of material acquisition. The paper focuses on Gerasim Zelić's Žitije, signalling how it is filled with descriptions of the struggle to reach an important social position and obtain material gain. Nevertheless, Zelić cannot be compared with contemporary adventurers, as he combines the aspiration of the Enlightenment with a strong faith in the concept of predestination, on one side, and the struggle to obtain personal gain with a strong commitment towards the common good, on the other.